Neurological manifestations and pathophysiological mechanisms of Covid-19 - Gaujac, Cristiano; Amaral, Regiane Cristina (ARCHIVES OF HEALTH INVESTIGATION, 2021)
Background - Severe acute respiratory syndrome coronavirus-2 is a novel, highly infectious coronavirus and the etiologic agent of Covid-19. The course of Covid-19 can range from mild flu-like symptoms to severe, life-threatening symptoms, especially when comorbidities are present. Increasing studies have reinforced the association between SARS-CoV-2 and various neurological manifestations, although the pathophysiological mechanisms remain uncertain. Objective - The aim of this paper was to briefly describe current findings on the relationship between SARS-CoV-2 pathophysiology and major CNS and Peripheral Nervous System (PNS) manifestations. Methods and Material - This work consists of a literature review based on the study of academic papers. To this end, the Pubmed platform was used to search for scientific articles, using the keywords: covid-19, coronavirus, physiopathology, neuronal symptoms. Results - out of 114,660 articles found, 94 were selected for this review. Conclusions - Periodic reviews collaborate in the constant updating and summarization of findings. Understanding the pathophysiology of SARS-CoV-2 on the SN and the link between the systems may lead to earlier and earlier diagnoses of neurological involvement, guide therapeutic management, prevent sequelae, and preserve lives.